2012
DOI: 10.1590/s0102-33062012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Atividade de enzimas antioxidantes e inibição do crescimento radicular de feijão caupi sob diferentes níveis de salinidade

Abstract: ABSTRACT(Activities of antioxidant enzymes and root growth inhibition in cowpea seedlings exposed to diff erent salt levels). Phenol peroxidase (POX) is a dual enzyme that is involved with hydrogen peroxide scavenging and lignin biosynthesis, contributing to growth inhibition by secondary wall thickening. In order to relate growth inhibition to salt-induced oxidative modulation, the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and POX were evaluated in cowpea roots under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
6
13
0
12
Order By: Relevance
“…The results obtained in the present study corroborate those found in cowpea grown under saline conditions, in response to increased POD activity (Maia et al 2012). Previous results from hypocotyls of corn seedlings also indicate that proteins were protected by increased CAT activity (Rosa et al 2005).…”
Section: Resultssupporting
confidence: 91%
“…The results obtained in the present study corroborate those found in cowpea grown under saline conditions, in response to increased POD activity (Maia et al 2012). Previous results from hypocotyls of corn seedlings also indicate that proteins were protected by increased CAT activity (Rosa et al 2005).…”
Section: Resultssupporting
confidence: 91%
“…A redução no crescimento das plântulas de guandu pelo aumento da salinidade foi expressivo, mesmo com o incremento observado nos teores de prolina, na parte aérea e nas raízes. A redução do potencial hídrico, induzida pelo PEG ou pelo sal, bem como os efeitos citotóxicos dos íons Na + e Cl -, no caso da salinidade, são responsáveis pela redução no crescimento das plântulas (Gordin et al, 2012;Maia et al, 2012).…”
Section: Resultsunclassified
“…A redução do potencial hídrico, induzida pelo sal, bem como, os efeitos citotóxicos dos íons Na + e Cl -são responsáveis pela redução na fitomassa e na densidade radicular das plântulas (Gordin et al, 2012;Maia et al, 2012). Esta informação é ratificada por Monteiro et al (2014) ao relatarem que em situações de toxidez por Na + e Cl -, a degradação de compostos celulares e a síntese de metabólitos indesejáveis podem promover redução drástica do crescimento.…”
Section: Summary Of Analysis Of Variance and Tukey Tests The Levels Ounclassified